2015
DOI: 10.1111/joa.12332
|View full text |Cite
|
Sign up to set email alerts
|

High doses of caffeine reduce in vivo osteogenic activity in prepubertal rats

Abstract: Caffeine adversely affects endochondral ossification during fetal skeletal growth, and results in increased incidence of delayed and abnormal fetal skeletal development. Chronic caffeine intake also decreases growth hormone secretion. Thus, it is conceivable that caffeine may disrupt bone growth during the peripubertal period. This study aimed to investigate the impact of high-caffeine consumption on bone growth throughout puberty. A total of 51 male rats (21 days old) were divided randomly into three groups: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(40 citation statements)
references
References 32 publications
(81 reference statements)
4
36
0
Order By: Relevance
“…Consistent with previous reports (5,8), we observed significant reductions in both body weight gain and food intake in caffeine-fed immature animals (Fig. 1A, 1C), indicating that reduced body weight gain can be attributed mainly to decreased food intake.…”
Section: Discussionsupporting
confidence: 93%
“…Consistent with previous reports (5,8), we observed significant reductions in both body weight gain and food intake in caffeine-fed immature animals (Fig. 1A, 1C), indicating that reduced body weight gain can be attributed mainly to decreased food intake.…”
Section: Discussionsupporting
confidence: 93%
“…We have also demonstrated that peripubertal exposure to caffeine clearly reduced the in vivo metabolic activity of the epiphyseal growth plate and markedly delayed the closing rate of the growth plate in young, rapidly growing animals (Shin et al. ). These negative influences of caffeine on the growth plate were observed in a dose‐dependent manner even after short‐term exposure (Choi et al.…”
Section: Introductionmentioning
confidence: 88%
“…The doses (120‐ or 180‐mg) levels were previously shown to inhibit the growth of long bones in immature male rats (Shin et al. ; Choi et al. ).…”
Section: Methodsmentioning
confidence: 99%
“…12 The highest dose (120 mg/kg) was chosen in this study based on the study, which showed no renal toxicity and demonstrated inhibition of long bone growth in prepubertal rats. 13 Thus, the highest dose in the study was chosen to investigate the effect of caffeine on longitudinal bone growth in a timedependent manner within the safe range of renal toxicity. The other two doses (20 and 60 mg/kg) were employed to determine whether the effects noted at the 120 mg dose were present in a dose-related manner.…”
Section: Animalsmentioning
confidence: 99%
“…In fact, based on Simmons Teen Survey data (an analysis of adolescent purchasing), the Mintel International Group reported in 2007 that 31% of [12][13][14][15][16][17] year-olds are reported to be regular consumers of energy drinks in the United States. 1 Among children and adolescents, energy drinks are popularly used for performance enhancement, increased concentration, and wakefulness.…”
Section: Introductionmentioning
confidence: 98%